Protection of stromal cell-derived factor 2 by heat shock protein 72 prevents oxaliplatin-induced cell death in oxaliplatin-resistant human gastric cancer cells. Issue 1 (1st August 2016) - Takahashi, Katsuyuki; Tanaka, Masako; Yashiro, Masakazu; Matsumoto, Masaki; Ohtsuka, Asuka; Nakayama, Keiichi I.; Izumi, Yasukatsu; Nagayama, Katsuya; Miura, Katsuyuki; Iwao, Hiroshi; Shiota, Masayuki
Highlights: Hsp72 and SDF-2 were overexpressed in OXA-resistant human gastric cancer cells. Hsp72 or SDF-2 silencing improved OXA sensitivity. SDF-2 was an Hsp72 client protein unique to OXA-resistant cancer cells. Hsp72 protected SDF-2 to avoid OXA-induced cell death. Abstract: Heat shock protein 72 (Hsp72) is a molecular chaperone that assists in the folding of nascent polypeptides and in the refolding of denatured proteins. In many cancers, Hsp72 is constitutively expressed at elevated levels, which can result in enhanced stress tolerance. Similarly, following treatment with anticancer drugs, Hsp72 binds to denatured proteins that may be essential for survival. We therefore hypothesized that Hsp72 client proteins may play a crucial role in drug resistance. Here, we aimed to identify proteins that are critical for oxaliplatin (OXA) resistance by analyzing human gastric cancer cell lines, as well as OXA-resistant cells via a mass spectrometry-based proteomic approach combined with affinity purification using anti-Hsp72 antibodies. Stromal cell-derived factor 2 (SDF-2) was identified as an Hsp72 client protein unique to OCUM-2M/OXA cells. SDF-2 was overexpressed in OXA-resistant cells and SDF-2 silencing promoted the apoptotic effects of OXA. Furthermore, Hsp72 prevented SDF-2 degradation in a chaperone activity-dependent manner. Together, our data demonstrate that Hsp72 protected SDF-2 to avoid OXA-induced cell death. We propose that inhibition of SDF-2 may comprise a novel therapeutic strategy to counteract OXA-resistant cancers.